The Impact Load Behavior of Reinforced Concrete Slab Samples Containing Waste Plastic Aggregate - Suhaib Yahya Kasim AL-Darzi; Kaythar A. Ibrahim; Oday Asal Salih (Tikrit Journal of Engineering Sciences)
In the present study, eight reinforced concrete slabs divided into four groups with two slabs per group were fabricated and tested under impact load, replacing their aggregate with 0%, 4%, 8%, and 16% of polyethylene terephthalate) PET). During the preparation process, PET materials increased the workability of fresh concrete by up to 16% and decreased the density by 9%. The compressive strength decreased by about 11.7%, 15.7%, and 19.9% using 4%, 8%, and 16% of PET, respectively. Splitting strength decreased by 7.2%, 17.4%, and 20.3% using 4%, 8%, and 16% of PET, respectively. Failure mode and deflection amplitude results showed that PET delayed the first cracks and reduced the crack lengths and width and crack spreading at failure. Also, impact resistance enhanced at the first crack and ultimate load stages when PET was used compared to normal concrete. The maximal and minimal displacement decreased with increasing PET proportion to 8% and 16%. The slabs were modeled using the finite element program SAP2000 with 4-node shell elements. The finite element (FE) analysis showed a similar deflection response as those experimentally obtained for all slabs. The deflection obtained by FE was less, about 15.5% and 19%, compared with all slabs experimentally tested except slab G2-2, which showed a higher deflection of about 16.3%.